Contra los métodos en el Derecho Internacional: una crítica a partir de su contribución para la realización de la función social de la dogmática jurídica (2011)
This article aims to analyze how methods contribute to accomplish doctrine's social function. In this context, methods are presented as tools to elaborate more precise answers for legal practice. The article wants to demonstrate the ontological impossibility of that task. Methods cannot give certainty to doctrinal arguments. To demonstrate this assumption through bibliographical research, the article presents the recent debate in international legal academy, and then starts with an example that serves as starting point to analyze the issue: the indeterminacy of the international customary law. Based on the best known methods, the article projects their answers to the practical issue concerning custom. The outcome is negative, reaffirming the initial hypothesis: we have to abandon the dream of a theoretical method laid on deductive models to give certainty for legal "science".